Ankle motion influences the external knee adduction moment and may predict who will respond to lateral wedge insoles?: an ancillary analysis from the SILK trial. Issue 8 (August 2015) - Chapman, G.J.; Parkes, M.J.; Forsythe, L.; Felson, D.T.; Jones, R.K.
Summary: Objective: Lateral wedge insoles are a potential simple treatment for medial knee osteoarthritis (OA) patients by reducing the external knee adduction moment (EKAM). However in some patients, an increase in their EKAM is seen. Understanding the role of the ankle joint complex in the response to lateral wedge insoles is critical in understanding and potentially identifying why some patients respond differently to lateral wedge insoles. Method: Participants with medial tibiofemoral OA underwent gait analysis whilst walking in a control shoe and a lateral wedge insole. We evaluated if dynamic ankle joint complex coronal plane biomechanical measures could explain and identify those participants that increased (biomechanical non-responder) or decreased (biomechanical responder) EKAM under lateral wedge conditions compared to the control shoe. Results: Of the 70 participants studied (43 male), 33% increased their EKAM and 67% decreased their EKAM. Overall, lateral wedge insoles shifted the centre of foot pressure laterally, increased eversion of the ankle/subtalar joint complex (STJ) and the eversion moment compared to the control condition. Ankle angle at peak EKAM and peak eversion ankle/STJ complex angle in the control condition predicted if individuals were likely to decrease EKAM under lateral wedge conditions. Conclusions: Coronal plane ankle/STJ complex biomechanical measures play a key role in reducing EKAM when wearing lateral wedge insoles. These findings may assist in the identification of those individuals that could benefit more from wearing lateral wedge insoles.